Phylogeography indicates incomplete genetic divergence among phenotypically differentiated montane forest populations of Atlapetes albinucha (Aves, Passerellidae) - Alberto Rocha-Méndez; Luis A. Sánchez-González; Enrique Arbeláez-Cortés; Adolfo G. Navarro-Sigüenza (ZooKeys, 2018)
The White-naped Brushfinch (Atlapetes albinucha) comprises up to eight allopatric subspecies mainly identified by the color of the underparts (gray vs. yellow belly). Yellow and gray bellied forms were long considered two different species (A. albinucha and A. gutturalis), but they are presently considered as one polytypic species. Previous studies in the genus Atlapetes have shown that the phylogeny, based on molecular data, is not congruent with characters such as coloration, ecology, or distributional patterns. The phylogeography of A. albinucha was analyzed using two mitochondrial DNA regions from samples including 24 different localities throughout montane areas from eastern Mexico to Colombia. Phylogeographic analyses using Bayesian inference, maximum likelihood and haplotype network revealed incomplete geographic structure. The genetic diversity pattern is congruent with a recent process of expansion, which is also supported by Ecological Niche Models (ENM) constructed for the species and projected into three past scenarios. Overall, the results revealed an incomplete genetic divergence among populations of A. albinucha in spite of the species’ ample range, which contrasts with previous results of phylogeographic patterns in other Neotropical montane forest bird species, suggesting idiosyncratic evolutionary histories for different taxa throughout the region.